Sensors for Everyday Life Environmental and Food Engineering - Mukhopadhyay, Subhas Chandra; Postolache, Octavian Adrian; Jayasundera, Krishanthi P.; Swain, Akshya K. (Smart Sensors, Measurement and Instrumentation, 2017)
This book offers an up-to-date overview of the concepts, modeling, technical and technological details and practical applications of different types of sensors, and discusses the trends of next generation of sensors and systems for environmental and food engineering. This book is aimed at researchers, graduate students, academics and industry professionals working in the field of environmental and food engineering, environmental monitoring, precision agriculture and food quality control.